Putusan Konstitusional Demokratis Terhadap Sengketa Pemilu Serentak 2024 - Wira Purwadi; Edi Gunawan; Nurlaila TQ; Gealby A R Roring; Andika Tangkudung; Renata Saputri (Fakultas Syariah dan Ekonomi Islam, 2022)
The Constitutional Court is a judicial institution that has the authority to resolve disputes over general election results. If the election law is not revised, then in 2024 there will be simultaneous elections and simultaneous regional elections. This study is to find out how the challenges of the Constitutional Court are in producing democratic constitutional decisions on 2024 Simultaneous election disputes and to find out how the role of the Constitutional Court in producing democratic constitutional decisions on 2024 Simultaneous election disputes. This type of research is legal research, in the development of legal research methods normative legal research and legal research empirical legal research must be combined or used both because combining the two studies will provide comprehensive research results. The institution as a judicial institution that adjudicates PHPU will face several challenges: 1) The readiness of the Constitutional Court in providing optimal services, 2) The political pressure of the presidential election is so hot, 3) the time and quality of the decision is short. The Constitutional Court's decision must truly reflect a fair decision within the framework of implementing constitutional democracy. A fair decision can only be given by a statesman judge, not merely a judge who is an adherent of the principle of legality who goes too far and becomes the mouthpiece of the law (bouche de la loi), which should be the mouthpiece of substantive justice